Development Of E-Module To Prevent And Early Detection OF Stunting Against Knowledge Of Pregnant Woman - Mutmainnah; Musni (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Stunting is a problem of malnutrition and is one of the common causes of morbidity and mortality in children, which is characterized by children who are smaller than their age. One strategy to overcome stunting is to provide educational interventions regarding stunting for pregnant women to increase knowledge about prevention and early detection of stunting using e-modules. This study aims to produce an e-module educational media product for preventing and early detection of stunting to increase knowledge of pregnant women. The research design uses R & D (Research and Development) and refers to the development stages of Borg & Gell to produce e-modules and the type of Quasi Experimental Research (Pre-Post Test Design) conducted on 44 pregnant women. Purposive sampling technique. Each pregnant woman was given a pre-post-test questionnaire along with an e-module for prevention and early detection of stunting. The feasibility test for the prevention and early detection of stunting e-module uses a Likert scale that is rated by the validator and for effectiveness, uses a Pre-Post Test questionnaire. The Wilcoxon test was used to determine the effectiveness of the stunting prevention and early detection e-module on increasing knowledge of pregnant women. The results showed that the value (p = 0.000 <0,05) which means that the stunting prevention and early detection e-module is effective in increasing the knowledge of pregnant women to prevent and early detection of stunting.